Victorian Beauty: Ruskin’s Changing Ideals - Professor Dinah Birch (19, 2023)
Ruskin, and to some extent his followers, is often seen as the great Victorian prophet of beauty. In his early writing he invests beauty with the force of religious truth. In a passage intended for the second volume of Modern Painters (1846), he writes of the power of an Alpine avalanche teaching him ‘what till then I had not known — the real meaning of the word Beautiful. With all that I had ever seen before — there had come mingled the associations of humanity — the exertion of human power — the action of human mind. The image of self had not been effaced in that of God […] . It was then that I understood that all which is the type of God’s attributes […] can turn the human soul from gazing upon itself […] and fix the spirit […] on the types of that which is to be its food for eternity; — this and this only is in the pure and right sense of the word beautiful’ (Works, IV, 364–65). But he was never entirely content with this definition, and only two years later writes of the landscape of the Jura in very different terms: ‘Those ever springing flowers and ever flowing streams had been dyed by the deep colours of human endurance, valour, and virtue; and the crests of the sable hills that rose against the evening sky received a deeper worship, because their far shadows fell eastward over the iron walls of Joux and the four-square keep of Granson’ (VIII, 223–24). In his later work he retreats from his youthful belief that the value of beauty is distinct from human character, claiming instead that ‘endurance is nobler than strength, and patience than beauty’ (XVI, 372). The perspective of his work shifts to the social and political, and he turns from the analysis of beauty to a critique of the circumstances that excluded men and women from its creation, or its presence. As he became more interested in justice, he grew less interested in beauty. To see the celebration of beauty as the primary motive of his work is to mistake the nature of its persistent challenge.